Debonding detection of defected CFRP-concrete interface using active microwave thermography. (15th April 2023) - Zou, Xingxing; Sneed, Lesley H.; Mirala, Ali; Al Qaseer, Mohammad Tayeb; Donnell, Kristen
Highlights: AMT can quickly detect initial defects at the CFRP-concrete interface. Initial defect can substantially decrease the interfacial load capacity. Initial defect can alter the interfacial debonding process and global load response. Interfacial damage formation was detected by change in slope of temperature contrast. Abstract: This study presents an investigation of non-destructive evaluation (NDE) of carbon fiber reinforced polymer (CFRP)-concrete interfacial debonding using a novel technology referred to as active microwave thermography (AMT). AMT utilizes microwave energy as a heating excitation to the structure and captures the anomalies of temperature contrast ( TC ) at the structure surface using a thermal camera. In this study, AMT was used first as an inspection method of CFRP-concrete joints. Comparative tests on CFRP-concrete joints with and without an initial man-made defect showed AMT can detect initial defects at the CFRP-concrete interface in around 15 s. Then, AMT was used to monitor the time-history progressive interfacial debonding process of the CFRP-concrete joints tested in direct shear under monotonically increasing loading. The test results showed that: (i) the initial defect at the CFRP-concrete interface can be detected by AMT quickly; (ii) the presence of an initial defect at the CFRP-concrete interface can substantially decrease the load-carrying capacity of the CFRP-concrete joint; (iii) the initial defect can alter the interfacial debonding process and global load response; and (iv) significant load drops, indicative of interfacial damage formation, could be detected by a change of slope of the local CFRP surface TC determined by AMT.